Multi-purpose UTHM Smart Matric System - Krishnamurti, Saravanan; Zohari, Mohd Hakimi (Progress in Engineering Application and Technology, 2023)
Smart cards have been available for so long, it have capacity and potential to make world advances in digital technology. Web-based systems are a particular type of software that allows users to interact with a remote server through a web browser interface and cloud database. Radio frequency identification is gaining popularity as an identification technology due to its low price, light weight, small size, and low maintenance costs. In this paper, the project consider the previously stated issues and discuss how RFID and smart card as an emerging technology can be integrated with web-based system developed using HTML, CSS, PHP, XAMPP and JavaScript which proposed to manage various functionality of matric card. A single smart matric card system with RFID integration has the potential to make student’s life easier.